3.2 kW, 0.22 nm narrow-linewidth MOPA configuration fiber laser with a homemade polarization-maintaining Yb-doped fiber - Liao, Shibiao; Luo, Tao; Xiao, Runheng; Cheng, Junjie; Shu, Chang; Zhang, Zhilun; Zhou, Yanyan; Xing, Yingbin; Li, Haiqing; Peng, Jinggang; Dai, Nengli; Li, Jinyan (Frontiers in Physics, 2023)
In this work, a narrow-linewidth linearly polarized fiber amplifier with a record output power of 3.2 kW was achieved based on a homemade polarization-maintaining Yb-doped fiber (PMYDF), corresponding to a slope efficiency of 79% and a 3 dB linewidth of 0.2227 nm. The experimental study on scaling mode instability (MI) threshold in PM fiber amplifiers was demonstrated by investigations of different numerical aperture (NA) PMYDFs. And the results reveal that the MI threshold is enhanced by more than 370 W for every 0.004 decrease in core NA. Increasing the seed linewidth from 0.0454 nm to 0.0976 nm by adding 200 m polarization maintaining Ge-doped fiber (PMGDF), the SBS threshold increased from 805 W to above 3.2 kW. By applying the MI suppression method, a double-eight-shaped aluminum plate was adopted to coil the gain fiber, and the MI threshold increased by more than 1100 W.